Evolutionary history of Kelp Gulls at the South Hemisphere - Linhares, Heloisa Helena; Frere, Esteban; Milliones, Ana; Pires de Mendonça Dantas, Gisele (Journal of Ornithology)
Kelp Gull is the most abundant gull species in the Southern Hemisphere, occurring in South America, Africa, New Zealand, Australia, Sub-Antarctic Island, and Antarctica Peninsula. There is no consensus about the number of subspecies; some studies proposed two and others six subspecies. Previous genetic studies with this species show low genetic diversity at mtDNA, in contrast to the high variability found in the nuclear gene. Thus, this study proposed to evaluate the subspecies of Kelp Gull through mtDNA, recovering the demographic history and population genetic structure throughout the South Hemisphere. For this, we sequenced Cytochrome b in 98 samples of Kelp Gull from Brazil, Argentina, and Antarctica, and added to the dataset 20 haplotypes available in GenBank. Bayesian Phylogeny did not support a clade in any subspecies proposed. However, it is possible to observe the genetic population structure of Kelp Gull in the Southern Hemisphere based on haplotype frequency. In addition, there is evidence that Kelp Gull lost genetic diversity, following population expansion during Holocene around 2500–3000 years ago. Fil: Linhares, Heloisa Helena. Pontifícia Universidade Católica de Minas Gerais; Brasil Fil: Frere, Esteban. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Milliones, Ana. Universidad Nacional de la Patagonia Austral; Argentina Fil: Pires de Mendonça Dantas, Gisele. Pontifícia Universidade Católica de Minas Gerais; Brasil